Association of Intraoperative Hemodynamic Parameters and Creatinine Levels with Early Graft Function Following Living Donor Kidney Transplantation: A Retrospective Study - Juni Kurniawaty; Novita Intan Arovah (Bali Journal of Anesthesiology)
Background: Intraoperative hemodynamic management is critical for optimizing graft function in kidney transplantation. The study aimed to investigate the association between intraoperative mean arterial pressure (MAP) and central venous pressure (CVP) with early graft function, as measured by postoperative serum creatinine levels, in patients undergoing living donor kidney transplantation. Materials and Methods: This retrospective study included 65 adult patients who underwent living donor renal transplantation. Serum creatinine levels were measured preoperatively and on postoperative days 1, 2, and 3. Repeated measures ANOVA was used to evaluate changes in creatinine levels over time and to assess the impact of MAP and CVP. Linear regression was used to identify predictors of postoperative creatinine levels. Results: The mean age of participants was 39.28 ± 12.83 years. A significant reduction (P < 0.001) in serum creatinine was observed from the preoperative period to each postoperative day, with no significant differences between postoperative days. Repeated measures ANOVA confirmed significant within-subject variation in creatinine levels (F = 26.74, P < 0.001). However, MAP (P = 0.730), CVP (P = 0.225), and their interaction (P = 0.628) were not significantly associated with changes in creatinine levels. On multivariable analysis, female sex was significantly associated with higher creatinine levels on days 1 and 3 (P = 0.035 and P = 0.049, respectively), and older age was associated with lower creatinine on day 3 (P = 0.010). Conclusion: In this cohort, early postoperative renal function improved significantly but was not associated with intraoperative MAP or CVP. These findings suggest that traditional hemodynamic targets may not reliably predict early graft function, and further research should explore alternative perioperative predictors.